Method for catalytic modification of magnesium-based hydrogen storage material by metal salt composite catalyst
By introducing a metal salt composite catalyst into magnesium-based hydrogen storage materials, and utilizing the combination of modifiers and metal salt compounds, the MgH2 particles are crushed after ball milling and mixing to promote deep hydrolysis reaction. This solves the problem of low hydrogen production rate during the hydrolysis process of magnesium-based hydrogen storage materials, and achieves high hydrogen production capacity and high hydrogen production rate.
Patent Information
- Application Number
- CN202411137014.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-19
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2044-08-19
AI Technical Summary
Existing magnesium-based hydrogen storage materials suffer from low hydrogen production rates and low hydrolysis yields during hydrolysis, mainly due to the formation of a dense magnesium hydroxide passivation layer that prevents further reactions.
A metal salt composite catalyst was ball-milled and mixed with magnesium-based hydrogen storage material. A modifier was then combined with the metal salt compound to prepare a catalyst that could improve the performance of hydrogen production by water electrolysis. The ball milling process refined the reactant particles, provided catalytic active sites, and released heat during the water electrolysis process to break down MgH2 particles and promote deep water electrolysis.
It significantly improves the hydrogen production capacity and rate of magnesium-based hydrogen storage materials, overcomes the influence of dense magnesium hydroxide passivation layer, and achieves efficient hydrogen production through hydrolysis.
Smart Images

Figure CN118877835B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of hydrogen storage materials technology, specifically relating to a method for catalytic modification of magnesium-based hydrogen storage materials using metal salt composite catalysts. Background Technology
[0002] Hydrogen energy, as a clean and efficient secondary energy source, boasts advantages such as widespread availability, zero pollution, high calorific value, high energy density, and storability and transportability. However, because hydrogen is a flammable and explosive gas, its storage and transportation technology is a key issue in the development of hydrogen energy. Solid-state hydrogen storage, with its advantages of high storage density and high safety, has become a new generation of hydrogen storage technology. Among them, solid-state hydrogen storage materials, represented by metal hydrides, can produce high-purity hydrogen when reacting with water. This method offers high yield, low cost, good stability, and high safety, and the produced hydrogen can be used as a mobile power source for fuel cells.
[0003] Among metal hydrides, magnesium-based hydrogen storage materials have become a promising hydrogen storage technology due to their high capacity and low cost. Magnesium is one of the most abundant light metal elements on Earth, inexpensive, low in density, and possesses excellent hydrogen storage performance. Magnesium absorbs hydrogen at high temperatures to transform into tetragonal magnesium hydride (MgH2). Therefore, using magnesium-based hydrides for hydrogen production via hydrolysis is a promising portable hydrogen production technology.
[0004] MgH2 in magnesium-based hydrides can react with water at room temperature and pressure to produce hydrogen gas and water-insoluble magnesium hydroxide. This reaction can proceed without a catalyst, releasing heat, and the theoretical hydrogen production is 1703 mL / g, reaching 15.2 wt% excluding water weight. However, without any additives, the byproduct Mg(OH)2 produced by hydrolysis exists in the form of a precipitate, forming a dense passivation layer on the surface of the particles. This prevents MgH2 from contacting water, severely limiting the further progress of the hydrolysis reaction, resulting in low hydrogen yield and hydrogen production rate.
[0005] To address the issue of low hydrogen yield and production rate caused by the formation of a dense magnesium hydroxide passivation layer on the surface of magnesium / magnesium hydride materials during hydrolysis, researchers have employed mechanical ball milling to combine calcium hydride and magnesium hydride to overcome the influence of the dense passivation film. However, when the calcium hydride is depleted, the passivation effect of magnesium hydroxide still exists, resulting in low hydrogen production efficiency.
[0006] Other researchers have mechanically ball-milled soluble salts such as magnesium chloride with magnesium hydride or elemental magnesium, utilizing the magnesium ion transfer from the soluble salts to generate magnesium hydroxide coating. However, magnesium-based hydrogen storage materials modified with soluble salts such as magnesium chloride still suffer from low hydrogen production rates and low hydrolysis yields during the hydrolysis hydrogen production process. Summary of the Invention
[0007] To address the problems of low hydrogen production rate and low hydrolysis yield in existing technologies that use metal hydrides or metal salts to modify magnesium-based hydrogen storage materials, the present invention aims to provide a method for modifying magnesium-based hydrogen storage materials using a metal salt composite catalyst.
[0008] To achieve the above objectives, the technical solution of the present invention is as follows.
[0009] This invention provides a method for catalytic modification of magnesium-based hydrogen storage materials using metal salt composite catalysts, comprising the following steps:
[0010] A metal salt composite catalyst is prepared by combining a modifier with a metal salt compound under a protective atmosphere; the metal salt compound is a salt compound containing at least one element selected from bismuth, vanadium, and iron; the modifier is an alkali metal, a metal hydride, or a metal borohydride; the mass ratio of the modifier to the metal salt compound is 1:0.02-4.
[0011] A modified magnesium-based hydrogen storage material was obtained by ball milling a metal salt composite catalyst with a magnesium-based hydrogen storage material.
[0012] This invention utilizes a modifier combined with a metal salt compound to prepare a metal salt composite catalyst that improves the performance of hydrogen production through water electrolysis. The prepared metal salt composite catalyst is then added to a magnesium-based hydrogen storage material and ball-milled to obtain a modified magnesium-based hydrogen storage material. During the hydrogen electrolysis process, the metal salt composite catalyst, acting as a highly active site, reacts first with water, releasing a large amount of heat. The resulting hydrogen gas and the volume expansion of the solid hydrolysis products cause further breakage of the MgH2 particles, generating fresh surfaces and accelerating the hydrolysis reaction. Simultaneously, the instantaneous increase in the temperature of the aqueous solution further increases the hydrogen production rate and inhibits the formation of Mg(OH)2, ultimately resulting in a higher hydrogen yield.
[0013] Preferably, the metal salt compound is a bismuth-containing salt compound.
[0014] Preferably, the metal salt compound is at least one of BiVO4, Bi(NO3)3, Bi2(SO4)3, BiCl3, BiPO4, Fe(NO3)3, and FeCl3.
[0015] Preferably, the mass ratio of the modifier to the metal salt compound is 1:0.02 to 1. For example, 1:0.02, 1:0.25, 1:1, 1:2, 1:3, 1:4, etc.
[0016] Preferably, the mass ratio of the metal salt composite catalyst to the magnesium-based hydrogen storage material is 0.05–0.3:0.7–0.95. For example, 0.05:0.95, 0.1:0.9, 0.2:0.8, 0.3:0.7, etc.
[0017] Preferably, the alkali metal is at least one selected from Li, Na, K, and Rb;
[0018] The metal hydride is a hydride of at least one of Li, Na, K, Rb, Mg, Ca, Sr, and Ba;
[0019] The metal borohydride is at least one of LiBH4, NaBH4, and KBH4.
[0020] Preferably, the modifier is at least one selected from Li, Na, K, LiH, NaH, KH, NaBH4, and KBH4.
[0021] Preferably, the specific preparation process of the metal salt composite catalyst is as follows: under a protective atmosphere, the modifier and the metal salt compound are stirred and mixed or ball-milled; the protective atmosphere is an inert gas or hydrogen.
[0022] Preferably, the composite is carried out in a solvent system; the solvent is selected from at least one of methanol, THF, ethanol, pentane, cyclohexane, and toluene.
[0023] The volume of the solvent accounts for 10% to 50% of the total volume of the modifier and the metal salt compound.
[0024] In this invention, the composite is preferably ball-milled; the ball-milling process is a prior art.
[0025] Preferably, the magnesium-based hydrogen storage material is any one of elemental magnesium, magnesium alloys, or their hydrides. Specifically, the magnesium alloy is a magnesium alloy formed by combining any one of Al, Fe, Co, Ni, Mn, V, Zn, Sn, In, La, Ce, K, and Na with Mg; and the percentage of magnesium in the magnesium alloy is >80%.
[0026] Preferably, the magnesium-based hydrogen storage material is MgH2.
[0027] The beneficial effects of this invention are:
[0028] 1. This invention utilizes a modifier combined with a metal salt compound to prepare a metal salt composite catalyst that can improve the hydrogen production performance through water electrolysis. The prepared metal salt composite catalyst is then added to a magnesium-based hydrogen storage material and ball-milled to mix it. This results in a modified magnesium-based hydrogen storage material with high hydrogen production capacity and an extremely fast hydrogen production rate, solving the problems of low hydrogen production rate and low water electrolysis yield in existing technologies that use metal hydrides or metal salts to modify magnesium-based hydrogen storage materials.
[0029] 2. The metal salt compound added in this invention has the effect of etching and decomposing the generated magnesium hydroxide, thereby overcoming the problem of forming a dense magnesium hydroxide passivation layer on the surface of magnesium / magnesium hydride materials during hydrolysis.
[0030] 3. This invention utilizes a metal salt composite catalyst obtained by combining a modifier and a metal salt compound as a catalyst, which is ball-milled and mixed with magnesium-based hydrogen storage materials. This process refines the reactant particles, provides active sites for the catalytic reaction, and simultaneously damages the magnesium hydroxide passivation layer, promoting the deep hydrolysis reaction of the magnesium-based hydrogen storage materials. Furthermore, the prepared modified magnesium-based hydrogen storage materials exhibit very high instantaneous hydrogen production rates and hydrogen yields, demonstrating high catalytic activity.
[0031] 4. The preparation process of the present invention is simple, easy to operate and scale up, easy to apply, and the raw materials are cheap and easy to obtain, making it especially suitable for special occasions where hydrogen needs to be produced on-site or used in portable applications. Attached Figure Description
[0032] Figure 1 The image shows a micrograph at the 1 μm scale of the modified magnesium-based hydrogen storage material prepared in Example 1.
[0033] Figure 2 The image shows a micrograph of the modified magnesium-based hydrogen storage material prepared in Example 1 at a scale of 100 nm.
[0034] Figure 3 The image shows a micrograph at the 1 μm scale of the modified magnesium-based hydrogen storage material prepared in Example 2.
[0035] Figure 4 The image shows a micrograph of the modified magnesium-based hydrogen storage material prepared in Example 2 at a scale of 50 nm.
[0036] Figure 5 The X-ray diffraction pattern of the modified magnesium-based hydrogen storage material prepared in Example 1.
[0037] Figure 6 The X-ray diffraction pattern of the modified magnesium-based hydrogen storage material prepared in Example 2 is shown.
[0038] Figure 7 The kinetic curves for hydrogen production by hydrolysis of the modified magnesium-based hydrogen storage material prepared in Example 1 are shown.
[0039] Figure 8 The kinetic curves for hydrogen production by hydrolysis of the modified magnesium-based hydrogen storage material prepared in Example 2 are shown. Detailed Implementation
[0040] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.
[0041] Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0042] This invention utilizes a modifier combined with a metal salt compound to prepare a metal salt composite catalyst that improves the hydrogen production performance through water electrolysis. The prepared metal salt composite catalyst is then added to a magnesium-based hydrogen storage material and ball-milled to obtain a modified magnesium-based hydrogen storage material. During the hydrogen electrolysis process, the metal salt composite catalyst, acting as a highly active site, reacts first with water, releasing a large amount of heat. The resulting hydrogen gas and the volume expansion of the solid hydrolysis products cause further breakage of the MgH2 particles, generating fresh surfaces and accelerating the hydrolysis reaction. Simultaneously, the instantaneous increase in the temperature of the aqueous solution further enhances the hydrogen production rate and inhibits the formation of Mg(OH)2, ultimately resulting in a higher hydrogen yield. This invention solves the problems of low hydrogen production rates and low hydrolysis yields in existing technologies using metal hydrides or metal salts to modify magnesium-based hydrogen storage materials.
[0043] This invention mainly utilizes a modifier to form a metal salt composite catalyst by combining it with a metal salt compound. The metal salt composite catalyst is then ball-milled and mixed with a magnesium-based hydrogen storage material. This process refines the reactant particles, provides active sites for catalytic reactions, and simultaneously damages the magnesium hydroxide passivation layer, promoting the deep hydrolysis reaction of the magnesium-based hydrogen storage material.
[0044] The added modifier is an alkali metal, metal hydride, or metal borohydride. During the hydrolysis hydrogen production process, the modifier comes into contact with water in the system, causing the modifier to release a large amount of heat during dissolution, which triggers the hydrolysis reaction of the magnesium-based hydrogen storage material. Since the hydrolysis of the magnesium-based hydrogen storage material is a highly exothermic reaction, this further increases the temperature of the reaction system, causing the reaction system to heat up rapidly and promoting the further hydrolysis of magnesium hydride.
[0045] The added metal salt compounds come into contact with and dissolve in the water during the hydrolysis hydrogen production process. The resulting anionic groups can effectively etch the dense magnesium hydroxide film produced by hydrolysis, promote the contact between the magnesium-based hydrogen storage material and water, and ensure the smooth progress of hydrolysis.
[0046] In the following embodiments, ball milling is carried out under a protective atmosphere. Dry ball milling or wet ball milling can be selected. The ball milling described in the embodiments of the present invention is preferably wet ball milling. The protective atmosphere uses an inert gas, such as argon. The ball milling process is existing technology. Specifically, the ball milling process involves rotating clockwise for 30 minutes and cooling for 15 minutes, then rotating counterclockwise for 30 minutes and cooling for 15 minutes, repeated 15 times. Preferably, the conditions for dry ball milling are: a ball-to-material ratio of 10–150:1, a ball milling speed of 50 rpm–600 rpm, and a ball milling time of 0.5 hours–60 hours. The conditions for wet ball milling are as follows: temperature 10℃~100℃, milling speed 50 rpm~600 rpm, milling time 0.5 hours~60 hours, and the solvent used for wet ball milling is at least one of methanol, THF, ethanol, pentane, cyclohexane, and toluene; specifically, the preferred solvent for wet ball milling is ethanol, and the amount of ethanol added is 10wt%~50wt% of the total mass of the solid material being milled.
[0047] The modified magnesium-based hydrogen storage material of this invention offers a simple and controllable hydrogen production operation when applied to water electrolysis. The added water can be deionized water or water containing inorganic salts, such as river water, lake water, or seawater. The water addition flow rate can be adjusted according to the required hydrogen flow rate, and the hydrogen release rate is also adjustable. It exhibits a high instantaneous hydrogen production capacity, making it particularly suitable for applications requiring rapid hydrogen supply.
[0048] Unless otherwise specified, the methods described in the following embodiments are conventional methods; the reagents and materials mentioned are commercially available unless otherwise specified.
[0049] Example 1
[0050] A method for catalytic modification of magnesium-based hydrogen storage materials using a metal salt composite catalyst, comprising the following steps:
[0051] Step 1, Preparation of metal salt composite catalyst:
[0052] In an inert atmosphere glove box, 0.5 g NaH and 0.5 g BiVO4 were mixed and added to a 50 mL steel ball mill jar. Ethanol with a total mass of 10 wt% of NaH and BiVO4 was added to the jar in a high-energy ball mill, with a ball-to-material ratio of 30:1. Simple mechanical ball milling was performed in the high-energy ball mill at a speed of 200 rpm for 22.5 hours. The resulting metal salt catalyst was denoted as NaH+BiVO4.
[0053] Step 2, Preparation of modified magnesium-based hydrogen storage materials:
[0054] In an inert atmosphere glove box, a metal salt composite catalyst and MgH2 were mixed at a mass ratio of 0.1:0.9 and added to a 50 mL steel ball mill jar. Then, 10 wt% of ethanol (the total mass of the metal salt composite catalyst and MgH2) was added to a high-energy ball mill, with a ball-to-material ratio of 30:1. Simple mechanical ball milling was performed at 200 rpm for 22.5 hours, ultimately yielding a modified magnesium-based hydrogen storage material.
[0055] Example 2
[0056] A method for catalytic modification of magnesium-based hydrogen storage materials using a metal salt composite catalyst, comprising the following steps:
[0057] Step 1, Preparation of metal salt composite catalyst:
[0058] In an inert atmosphere glove box, 0.5 g NaH and 0.5 g Bi(NO3)3 were mixed and added to a 50 mL steel ball mill jar. Ethanol with a total mass of 10 wt% of NaH and Bi(NO3)3 was added to a high-energy ball mill, with a ball-to-material ratio of 30:1. Simple mechanical ball milling was performed using a high-energy ball mill at a speed of 200 rpm for 22.5 hours. The resulting metal salt composite catalyst was denoted as NaH+Bi(NO3)3.
[0059] Step 2, Preparation of modified magnesium-based hydrogen storage materials:
[0060] In an inert atmosphere glove box, a metal salt composite catalyst and MgH2 were mixed at a mass ratio of 0.1:0.9 and added to a 50 mL steel ball mill jar. Ethanol at a total mass of 10 wt% of the metal salt composite catalyst and MgH2 was added to a high-energy ball mill, with a ball-to-material ratio of 30:1. Simple mechanical ball milling was performed in the high-energy ball mill at a speed of 200 rpm for 22.5 hours, finally yielding a modified magnesium-based hydrogen storage material.
[0061] Example 3
[0062] Step 1, Preparation of metal salt composite catalyst:
[0063] In an inert atmosphere glove box, 0.5 g NaH and 0.5 g Bi2(SO4)3 were mixed and added to a 50 mL steel ball mill jar. Ethanol with a total mass of 10 wt% of NaH and Bi2(SO4)3 was added to a high-energy ball mill, with a ball-to-material ratio of 30:1. Simple mechanical ball milling was performed using a high-energy ball mill at a speed of 200 rpm for 22.5 hours. The resulting metal salt catalyst was denoted as NaH+Bi2(SO4)3.
[0064] Step 2, Preparation of modified magnesium-based hydrogen storage materials:
[0065] In an inert atmosphere glove box, a metal salt composite catalyst and MgH2 were mixed at a mass ratio of 0.1:0.9 and added to a 50 mL steel ball mill jar. Ethanol at a total mass of 10 wt% of the metal salt composite catalyst and MgH2 was added to a high-energy ball mill, with a ball-to-material ratio of 30:1. Simple mechanical ball milling was performed in the high-energy ball mill at a speed of 200 rpm for 22.5 hours, finally yielding a modified magnesium-based hydrogen storage material.
[0066] Example 4
[0067] A method for catalytic modification of magnesium-based hydrogen storage materials using a metal salt composite catalyst, comprising the following steps:
[0068] Step 1, Preparation of metal salt composite catalyst:
[0069] In an inert atmosphere glove box, 0.5 g NaH and 0.5 g BiCl3 were mixed and added to a 50 mL steel ball mill jar. Ethanol with a total mass of 10 wt% of NaH and BiCl3 was added to a high-energy ball mill, with a ball-to-material ratio of 30:1. Simple mechanical ball milling was performed using a high-energy ball mill at a speed of 200 rpm for 22.5 hours. The resulting metal salt catalyst was denoted as NaH+BiCl3.
[0070] Step 2, Preparation of modified magnesium-based hydrogen storage materials:
[0071] In an inert atmosphere glove box, a metal salt composite catalyst and MgH2 were mixed at a mass ratio of 0.1:0.9 and added to a 50 mL steel ball mill jar. Ethanol at a total mass of 10 wt% of the metal salt composite catalyst and MgH2 was added to a high-energy ball mill, with a ball-to-material ratio of 30:1. Simple mechanical ball milling was performed in the high-energy ball mill at a speed of 200 rpm for 22.5 hours, finally yielding a modified magnesium-based hydrogen storage material.
[0072] Example 5
[0073] A method for catalytic modification of magnesium-based hydrogen storage materials using a metal salt composite catalyst, comprising the following steps:
[0074] Step 1, Preparation of metal salt composite catalyst:
[0075] In an inert atmosphere glove box, 0.5 g NaH and 0.5 g BiPO4 were mixed and added to a 50 mL steel ball mill jar. Ethanol with a total mass of 10 wt% of NaH and BiPO4 was added to the jar in a high-energy ball mill, with a ball-to-material ratio of 30:1. Simple mechanical ball milling was performed in the high-energy ball mill at a speed of 200 rpm for 22.5 hours. The resulting metal salt catalyst was denoted as NaH+BiPO4.
[0076] Step 2, Preparation of modified magnesium-based hydrogen storage materials:
[0077] In an inert atmosphere glove box, a metal salt composite catalyst and MgH2 were mixed at a mass ratio of 0.1:0.9 and added to a 50 mL steel ball mill jar. Ethanol at a total mass of 10 wt% of the metal salt composite catalyst and MgH2 was added to a high-energy ball mill, with a ball-to-material ratio of 30:1. Simple mechanical ball milling was performed in the high-energy ball mill at a speed of 200 rpm for 22.5 hours, finally yielding a modified magnesium-based hydrogen storage material.
[0078] Example 6
[0079] A method for catalytic modification of magnesium-based hydrogen storage materials using a metal salt composite catalyst, comprising the following steps:
[0080] Step 1, Preparation of metal salt composite catalyst:
[0081] In an inert atmosphere glove box, 0.5 g NaH and 0.5 g Fe(NO3)3 were mixed and added to a 50 mL steel ball mill jar; then, 10 wt% of ethanol (total mass of NaH and Fe(NO3)3) was added to a high-energy ball mill with a ball-to-material ratio of 30:1; simple mechanical ball milling was performed at a high-energy ball mill at a speed of 200 rpm for 22.5 hours; finally, a metal salt composite catalyst, denoted as NaH+Fe(NO3)3, was obtained.
[0082] Step 2, Preparation of modified magnesium-based hydrogen storage materials:
[0083] In an inert atmosphere glove box, a metal salt composite catalyst and MgH2 were mixed at a mass ratio of 0.1:0.9 and added to a 50 mL steel ball mill jar. Ethanol at a total mass of 10 wt% of the metal salt composite catalyst and MgH2 was added to a high-energy ball mill, with a ball-to-material ratio of 30:1. Simple mechanical ball milling was performed in the high-energy ball mill at a speed of 200 rpm for 22.5 hours, finally yielding a modified magnesium-based hydrogen storage material.
[0084] Example 7
[0085] A method for catalytic modification of magnesium-based hydrogen storage materials using a metal salt composite catalyst, comprising the following steps:
[0086] Step 1, Preparation of metal salt composite catalyst:
[0087] In an inert atmosphere glove box, 0.5 g NaH and 0.5 g FeCl3 were mixed and added to a 50 mL steel ball mill jar; then, 10 wt% of ethanol (total mass of NaH and FeCl3) was added to a high-energy ball mill, with a ball-to-material ratio of 30:1; simple mechanical ball milling was performed using a high-energy ball mill at a speed of 200 rpm for 22.5 hours; finally, a metal salt composite catalyst, denoted as NaH+FeCl3, was obtained.
[0088] Step 2, Preparation of modified magnesium-based hydrogen storage materials:
[0089] In an inert atmosphere glove box, a metal salt composite catalyst and MgH2 were mixed at a mass ratio of 0.1:0.9 and added to a 50 mL steel ball mill jar. Ethanol at a total mass of 10 wt% of the metal salt composite catalyst and MgH2 was added to a high-energy ball mill, with a ball-to-material ratio of 30:1. Simple mechanical ball milling was performed in the high-energy ball mill at a speed of 200 rpm for 22.5 hours, finally yielding a modified magnesium-based hydrogen storage material.
[0090] Example 8
[0091] A method for catalytic modification of magnesium-based hydrogen storage materials using a metal salt composite catalyst, comprising the following steps:
[0092] Step 1, Preparation of metal salt composite catalyst:
[0093] In an inert atmosphere glove box, 0.5 g KBH4 and 0.5 g BiVO4 were mixed and added to a 50 mL steel ball mill jar; then, 10 wt% of ethanol (total mass of NaH and BiVO4) was added to a high-energy ball mill, with a ball-to-material ratio of 30:1; simple mechanical ball milling was performed using a high-energy ball mill at a speed of 200 rpm for 22.5 hours; finally, a metal salt composite catalyst, denoted as KBH4+BiVO4, was obtained.
[0094] Step 2, Preparation of modified magnesium-based hydrogen storage materials:
[0095] In an inert atmosphere glove box, a metal salt composite catalyst and MgH2 were mixed at a mass ratio of 0.1:0.9 and added to a 50 mL steel ball mill jar. Ethanol at a total mass of 10 wt% of the metal salt composite catalyst and MgH2 was added to a high-energy ball mill, with a ball-to-material ratio of 30:1. Simple mechanical ball milling was performed in the high-energy ball mill at a speed of 200 rpm for 22.5 hours, finally yielding a modified magnesium-based hydrogen storage material.
[0096] Example 9
[0097] A method for catalytic modification of magnesium-based hydrogen storage materials using a metal salt composite catalyst, comprising the following steps:
[0098] Step 1, Preparation of metal salt composite catalyst:
[0099] In an inert atmosphere glove box, 0.5 g Na and 0.5 g Bi(NO3)3 were mixed and added to a 50 mL steel ball mill jar; then, 10 wt% of ethanol (total mass of NaH and Bi(NO3)3) was added to a high-energy ball mill with a ball-to-material ratio of 30:1; simple mechanical ball milling was performed at a high-energy ball mill at a speed of 200 rpm for 22.5 hours; finally, a metal salt composite catalyst, denoted as Na+Bi(NO3)3, was obtained.
[0100] Step 2, Preparation of modified magnesium-based hydrogen storage materials:
[0101] In an inert atmosphere glove box, a metal salt composite catalyst and MgH2 were mixed at a mass ratio of 0.1:0.9 and added to a 50 mL steel ball mill jar. Ethanol at a total mass of 10 wt% of the metal salt composite catalyst and MgH2 was added to a high-energy ball mill, with a ball-to-material ratio of 30:1. Simple mechanical ball milling was performed in the high-energy ball mill at a speed of 200 rpm for 22.5 hours, finally yielding a modified magnesium-based hydrogen storage material.
[0102] Example 10
[0103] A method for catalytic modification of magnesium-based hydrogen storage materials using a metal salt composite catalyst, comprising the following steps:
[0104] Step 1, Preparation of metal salt composite catalyst:
[0105] In an inert atmosphere glove box, 0.8 g NaH and 0.2 g Bi(NO3)3 were mixed and added to a 50 mL steel ball mill jar at a ball-to-material ratio of 30:1. Simple mechanical ball milling was performed using a high-energy ball mill, with the milling process consisting of 30 min forward rotation followed by 15 min cooling, then 30 min reverse rotation followed by 15 min cooling, repeated 15 times. The resulting metal salt composite catalyst was denoted as NaH+Bi(NO3)3.
[0106] Step 2, Preparation of modified magnesium-based hydrogen storage materials:
[0107] In an inert atmosphere glove box, a metal salt composite catalyst and MgH2 were mixed at a mass ratio of 0.1:0.9 and added to a 50 mL steel ball mill jar. Ethanol at a total mass of 10 wt% of the metal salt composite catalyst and MgH2 was added to a high-energy ball mill, with a ball-to-material ratio of 30:1. Simple mechanical ball milling was performed in the high-energy ball mill at a speed of 200 rpm for 22.5 hours, finally yielding a modified magnesium-based hydrogen storage material.
[0108] Example 11
[0109] A method for catalytic modification of magnesium-based hydrogen storage materials using a metal salt composite catalyst, comprising the following steps:
[0110] Step 1, Preparation of metal salt composite catalyst:
[0111] In an inert atmosphere glove box, 0.2 g NaH and 0.8 g Bi(NO3)3 were mixed and added to a 50 mL steel ball mill jar at a ball-to-material ratio of 30:1. Simple mechanical ball milling was performed using a high-energy ball mill, with the milling process consisting of 30 min forward rotation followed by 15 min cooling, then 30 min reverse rotation followed by 15 min cooling, repeated 15 times. The resulting metal salt composite catalyst was denoted as NaH+Bi(NO3)3.
[0112] Step 2, Preparation of modified magnesium-based hydrogen storage materials:
[0113] In an inert atmosphere glove box, a metal salt composite catalyst and MgH2 were mixed at a mass ratio of 0.1:0.9 and added to a 50 mL steel ball mill jar. Ethanol at a total mass of 10 wt% of the metal salt composite catalyst and MgH2 was added to a high-energy ball mill, with a ball-to-material ratio of 30:1. Simple mechanical ball milling was performed in the high-energy ball mill at a speed of 200 rpm for 22.5 hours, finally yielding a modified magnesium-based hydrogen storage material.
[0114] Example 12
[0115] A method for catalytic modification of magnesium-based hydrogen storage materials using a metal salt composite catalyst, comprising the following steps:
[0116] Step 1, Preparation of metal salt composite catalyst:
[0117] In an inert atmosphere glove box, 0.5 g NaH and 0.5 g Bi(NO3)3 were mixed and added to a 50 mL steel ball mill jar at a ball-to-material ratio of 30:1. Simple mechanical ball milling was performed using a high-energy ball mill, with the milling process consisting of 30 min forward rotation followed by 15 min cooling, then 30 min reverse rotation followed by 15 min cooling, repeated 15 times. The resulting metal salt composite catalyst was denoted as NaH+Bi(NO3)3.
[0118] Step 2, Preparation of modified magnesium-based hydrogen storage materials:
[0119] In an inert atmosphere glove box, a metal salt composite catalyst and MgH2 were mixed at a mass ratio of 0.3:0.7 and added to a 50 mL steel ball mill jar. Ethanol at a total mass of 10 wt% of the metal salt composite catalyst and MgH2 was added to a high-energy ball mill, with a ball-to-material ratio of 30:1. Simple mechanical ball milling was performed in the high-energy ball mill at a speed of 200 rpm for 22.5 hours, finally yielding a modified magnesium-based hydrogen storage material.
[0120] Example 13
[0121] A method for catalytic modification of magnesium-based hydrogen storage materials using a metal salt composite catalyst, comprising the following steps:
[0122] Step 1, Preparation of metal salt composite catalyst:
[0123] In an inert atmosphere glove box, 0.5 g NaH and 0.5 g Bi(NO3)3 were mixed and added to a 50 mL steel ball mill jar at a ball-to-material ratio of 30:1. Simple mechanical ball milling was performed using a high-energy ball mill, with the milling process consisting of 30 min forward rotation followed by 15 min cooling, then 30 min reverse rotation followed by 15 min cooling, repeated 15 times. The resulting metal salt composite catalyst was denoted as NaH+Bi(NO3)3.
[0124] Step 2, Preparation of modified magnesium-based hydrogen storage materials:
[0125] In an inert atmosphere glove box, a metal salt composite catalyst and MgH2 were mixed at a mass ratio of 0.05:0.95 and added to a 50 mL steel ball mill jar. Ethanol with a total mass of 10 wt% of the metal salt composite catalyst and MgH2 was added to a high-energy ball mill, with a ball-to-material ratio of 30:1. Simple mechanical ball milling was carried out in the high-energy ball mill at a speed of 200 rpm for 22.5 hours, finally yielding a modified magnesium-based hydrogen storage material.
[0126] The modified magnesium-based hydrogen storage material prepared in the above embodiments was subjected to microscopic image analysis, X-ray diffraction analysis, and hydrolysis hydrogen production experiments, and the hydrogen production rate was tested.
[0127] Test 1: Microscopic image analysis.
[0128] Microscopic image analysis was performed on the modified magnesium-based hydrogen storage material prepared in Example 1, and the results are shown in the figure. Figure 1 and Figure 2 The results showed that after ball milling, the metal salt composite catalyst was uniformly distributed on the surface of MgH2.
[0129] Microscopic image analysis was performed on the modified magnesium-based hydrogen storage material prepared in Example 2, and the results are shown in the figure. Figure 3 and Figure 4 The results showed that after ball milling, the metal salt composite catalyst was uniformly distributed on the surface of MgH2.
[0130] Microscopic image analysis of Examples 3 to 14 yielded results consistent with those of Examples 1 and 2. This demonstrates that the ball milling process in the above examples effectively distributes the metal salt composite catalyst uniformly on the surface of MgH2.
[0131] Test 2: X-ray diffraction analysis.
[0132] X-ray diffraction analysis was performed on the modified magnesium-based hydrogen storage material prepared in Example 1. The results are shown in the figure. Figure 5 .
[0133] X-ray diffraction analysis was performed on the modified magnesium-based hydrogen storage material prepared in Example 2. The results are shown in the figure. Figure 6 .
[0134] from Figure 5 and Figure 6 As can be seen, the ball-milling product consists of MgH2 and different metal salts. During hydrolysis, the metal salts dissolve in water and release a certain amount of heat, which catalyzes and enhances the hydrolysis performance of magnesium-based materials under the synergistic effect of anions, cations, and microheat. Notably, a new ball-milling product, NaMgH3, is formed during the ball-milling process. This substance, as an active agent, further promotes the hydrolysis of magnesium-based materials.
[0135] Test 3: Hydrogen production experiment via hydrolysis.
[0136] To investigate the effect of different metal salt composite catalysts on the hydrogen production rate by hydrolysis, hydrogen production experiments were conducted on the modified magnesium-based hydrogen storage materials prepared in Examples 1 to 7, and the hydrogen production rate was tested. The results are shown in [Figure Number]. Figure 7 and Figure 8 And Table 1.
[0137] Table 1 Effect of different metal salt composite catalysts on the rate of hydrogen production from hydrolysis
[0138]
[0139] Note: Hydrogen production is the volume of hydrogen gas produced per g of MgH2.
[0140] As shown in Table 1, the modified magnesium-based hydrogen storage materials prepared using different metal salt compounds in the embodiments of the present invention were subjected to hydrolysis to produce hydrogen, and the hydrogen production rate was recorded using a flow meter. The hydrogen production rate ranged from 987.6 mL / g to 1401.8 mL / g. Among them, the modified magnesium-based hydrogen storage materials prepared with BiVO4, Bi(NO3)3, Bi2(SO4)3, BiCl3, BiPO4, and Fe(NO3)3 all had hydrogen production rates above 1200 mL / g, and the modified magnesium-based hydrogen storage materials prepared with Bi-containing metal salt compounds had the highest hydrogen production rate.
[0141] For the hydrogen production rate per minute, the modified magnesium-based hydrogen storage materials prepared in Examples 1-7 have a hydrogen production rate of 169 mL·g⁻¹ per minute. -1 min -1 ~212.4 mL·g -1 min -1 Among them, the modified magnesium-based hydrogen storage materials prepared from BiVO4, Bi(NO3)3, Bi2(SO4)3, BiCl3, and Fe(NO3)3 all had a hydrogen production rate of 180 mL·g per minute. -1 min -1 Of the above, the modified magnesium-based hydrogen storage material prepared from Bi2(SO4)3 has the highest hydrogen production.
[0142] Regarding the instantaneous reaction rate, the modified magnesium-based hydrogen storage materials prepared in Examples 1-7 have an instantaneous reaction rate of 1476 mL·g. -1 min -1 ~1984mL·g -1 min -1 Among them, the instantaneous reaction rates of the modified magnesium-based hydrogen storage materials prepared from BiVO4, Bi(NO3)3, Bi2(SO4)3, BiCl3, BiPO4, and FeCl3 were all above 1500 mL·g. -1 min -1 Of the above, the modified magnesium-based hydrogen storage material prepared with BiVO4 has the highest hydrogen production.
[0143] The above analysis shows that modified magnesium-based hydrogen storage materials prepared from Bi-containing metal salt compounds have high hydrogen production capacity and extremely fast hydrogen production rate.
[0144] Test 4: Hydrogen production experiment via hydrolysis.
[0145] To investigate the effect of different modifiers on the hydrogen production rate by hydrolysis, hydrogen production experiments were conducted on the modified magnesium-based hydrogen storage materials prepared in Examples 1, 2, 8 and 9, and the hydrogen production rate was tested. The results are shown in Table 2.
[0146] Table 2 Effect of different modifiers on the rate of hydrogen production from hydrolysis
[0147]
[0148] Note: Hydrogen production is the volume of hydrogen gas produced per g of MgH2.
[0149] As shown in Table 2, compared with KBH4, the modified magnesium-based hydrogen storage material prepared with NaH as the modifier has relatively higher hydrogen production capacity and hydrogen production rate. Compared with NaH, the modified magnesium-based hydrogen storage material prepared with Na as the modifier has a relatively higher 1-minute hydrogen production rate; however, in terms of hydrogen production capacity and instantaneous reaction rate, the modified magnesium-based hydrogen storage material prepared with NaH as the modifier has relatively higher hydrogen production capacity and instantaneous reaction rate.
[0150] The above analysis shows that the modified magnesium-based hydrogen storage material prepared by using NaH as a modifier has a high hydrogen production capacity and an extremely fast hydrogen production rate.
[0151] Test 5: Hydrogen production experiment via hydrolysis.
[0152] To investigate the effect of different mass ratios of modifier to metal salt compound on the performance of modified magnesium-based hydrogen storage materials, hydrogen production experiments were conducted on the modified magnesium-based hydrogen storage materials prepared in Examples 2, 10, and 11, and the hydrogen production rate was tested. The results are shown in Table 3.
[0153] Table 3. Effect of different mass ratios of modifier to metal salt compound on the rate of hydrogen production from hydrolysis.
[0154]
[0155] Note: Hydrogen production is the volume of hydrogen gas produced per g of MgH2.
[0156] As can be seen from the results in Table 3, the amount of hydrogen produced first increases and then decreases with the increase of Bi(NO3)3 dosage; the hydrogen production rate at 1 min shows a gradual decreasing trend; and the instantaneous reaction rate also shows a gradual decreasing trend.
[0157] Therefore, it can be seen that the modified magnesium-based hydrogen storage materials prepared with Bi(NO3)3 in the range of 0.2g to 0.5g exhibit relatively good hydrogen production performance. Among them, the modified magnesium-based hydrogen storage material prepared with Bi(NO3)3 at a dosage of 0.2g has an extremely fast hydrogen production rate, while the modified magnesium-based hydrogen storage material prepared with Bi(NO3)3 at a dosage of 0.5g has a high hydrogen production capacity.
[0158] Test 6: Hydrogen production experiment via hydrolysis.
[0159] To investigate the effect of different mass ratios of metal salt composite catalysts to MgH2 on the performance of modified magnesium-based hydrogen storage materials, hydrogen production experiments were conducted on the modified magnesium-based hydrogen storage materials prepared in Examples 2, 12, and 13, and the hydrogen production rate was tested. The results are shown in Table 4.
[0160] Table 4. Effect of different mass ratios of metal salt composite catalyst to MgH2 on the hydrolysis hydrogen production rate.
[0161]
[0162] Note: Hydrogen production is the volume of hydrogen gas produced per g of MgH2.
[0163] As can be seen from the results in Table 4, the amount of hydrogen produced first increases and then decreases with the increase of MgH2 dosage; the hydrogen production rate at 1 min shows a gradual decreasing trend; and the instantaneous reaction rate also shows a gradual decreasing trend.
[0164] Therefore, it can be seen that modified magnesium-based hydrogen storage materials prepared with a mass ratio of metal salt composite catalyst to MgH2 in the range of 0.1–0.3:0.7–0.9 exhibit relatively good hydrogen production performance. Among them, the modified magnesium-based hydrogen storage material prepared with a mass ratio of metal salt composite catalyst to MgH2 of 0.3:0.7 has an extremely fast hydrogen production rate; the modified magnesium-based hydrogen storage material prepared with a mass ratio of metal salt composite catalyst to MgH2 of 0.1:0.9 has a high hydrogen production capacity.
[0165] The above analysis shows that by selecting appropriate modifiers, metal salt compounds, and suitable raw material ratios, the embodiments of the present invention can help improve the hydrogen production capacity and hydrogen production rate of the prepared modified magnesium-based hydrogen storage materials.
[0166] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for catalytic modification of magnesium-based hydrogen storage materials using a metal salt composite catalyst, comprising the following steps: Metal salt composite catalysts were prepared by combining modifiers with metal salt compounds under a protective atmosphere. The metal salt compound is at least one selected from BiVO4, Bi(NO3)3, Bi2(SO4)3, BiCl3, BiPO4, Fe(NO3)3, and FeCl3; the modifier is an alkali metal, a metal hydride, or a metal borohydride; the mass ratio of the modifier to the metal salt compound is 1:0.02~1. A modified magnesium-based hydrogen storage material is obtained by ball milling a metal salt composite catalyst with a magnesium-based hydrogen storage material. The mass ratio of the metal salt composite catalyst to the magnesium-based hydrogen storage material is 0.05-0.3:0.7-0.
95.
2. The method for catalytic modification of magnesium-based hydrogen storage materials using metal salt composite catalysts according to claim 1, characterized in that, The alkali metal is at least one of Li, Na, K, and Rb; The metal hydride is a hydride of at least one of Li, Na, K, Rb, Mg, Ca, Sr, and Ba; The metal borohydride is at least one of LiBH4, NaBH4, and KBH4.
3. The method for catalytic modification of magnesium-based hydrogen storage materials using metal salt composite catalysts according to claim 2, characterized in that, The modifier is at least one of Li, Na, K, LiH, NaH, KH, NaBH4, and KBH4.
4. The method for catalytic modification of magnesium-based hydrogen storage materials using metal salt composite catalysts according to claim 1, characterized in that, The specific preparation process of metal salt composite catalysts is as follows: Under a protective atmosphere, the modifier and the metal salt compound are stirred or ball-milled; the protective atmosphere is an inert gas or hydrogen.
5. The method for catalytic modification of magnesium-based hydrogen storage materials using metal salt composite catalysts according to claim 4, characterized in that, The composite process is carried out in a solvent system; the solvent is selected from at least one of methanol, THF, ethanol, pentane, cyclohexane, and toluene. The volume of the solvent accounts for 10% to 50% of the total volume of the modifier and the metal salt compound.
6. The method for catalytic modification of magnesium-based hydrogen storage materials using metal salt composite catalysts according to claim 1, characterized in that, The magnesium-based hydrogen storage material is MgH2.
Citation Information
Patent Citations
Catalyst, preparation method of catalyst, hydrogen storage material containing catalyst and preparation method of hydrogen storage material
CN115957734A
Method for Fabricating Magnesium-Based Hydrogen Storage Material
US20080111105A1
